1995
DOI: 10.1046/j.1365-313x.1995.8060933.x
|View full text |Cite
|
Sign up to set email alerts
|

The coat protein of potato virus X is a strain‐specific elicitor of Rx1‐mediated virus resistance in potato

Abstract: The Rx1 gene in potato confers extreme resistance to potato virus X (PVX). To investigate the mechanism and elicitation of Rx resistance, protoplasts of potato cv. Cara (Rx1 genotype) and Maris Bard (rx1 genotype) were inoculated with PVX and tobacco mosaic virus (TMV). At 24 h post-inoculation in Maris Bard protoplasts there was at least 100-fold more PVX RNA than in protoplasts of Cara. TMV RNA accumulated to the same level in both types of protoplast. However, when the TMV was inoculated together with PVX t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(108 citation statements)
references
References 0 publications
4
98
1
2
Order By: Relevance
“…We therefore concluded that SPRYSEC-19 suppressed elicitor-dependent programmed cell death mediated by Gpa2. Gpa2 is highly similar to the virus resistance protein Rx1 that recognizes the coat protein of the avirulent Potato virus X (PVX) strain UK106 (Cp106; Bendahmane et al, 1995). Cp106 shares no sequence similarity with GpRBP-1 or with other SPRYSEC effectors.…”
Section: Sprysec-19 Selectively Suppresses Cc-nb-lrr-mediated Programmedmentioning
confidence: 99%
“…We therefore concluded that SPRYSEC-19 suppressed elicitor-dependent programmed cell death mediated by Gpa2. Gpa2 is highly similar to the virus resistance protein Rx1 that recognizes the coat protein of the avirulent Potato virus X (PVX) strain UK106 (Cp106; Bendahmane et al, 1995). Cp106 shares no sequence similarity with GpRBP-1 or with other SPRYSEC effectors.…”
Section: Sprysec-19 Selectively Suppresses Cc-nb-lrr-mediated Programmedmentioning
confidence: 99%
“…The CC domain with a coiled-coil structure is implicated in specific interactions with other proteins and also facilitates dimerization [12]. The CC-NB-LRR protein Rx of potato is found to interact with the Potato virus X (PVX) coat protein conferring resistance to PVX [13] and the Arabidopsis RPS4 gene is involved in resistance to Avr Rps4 of bacterial pathogens [14]. Based on the conserved domains of known R-genes across plant species, novel resistance gene analogues (RGAs) have been isolated from diverse plants by degenerate oligonucleotide primer based PCR approach [15].…”
Section: Introductionmentioning
confidence: 99%
“…andigena and Rx2 from S. acaule (Ritter et al, 1991). The open reading frames of Rx1 and Rx2 show 95% identity at the nucleotide level (Bendahmane et al, 1995). Farnham and Baulcombe (2006) demonstrated that the wild-type potato NBS-LRR protein Rx confers resistance against a single strain of PVX.…”
Section: Genes Associated With Er Type Resistancementioning
confidence: 98%
“…In potato, ER to PVX is controlled by the dominant genes Rx1 and Rx2. Rx confers a race-specific resistance to PVX by recognition of the viral coat protein (Bendahmane et al, 1995). The gene Rx1 is located on chromosome XII and the gene Rx2 on chromosome V. On the basis of pedigree analysis, it was assumed that Rx1 derived from S. tuberosum subsp.…”
Section: Genes Associated With Er Type Resistancementioning
confidence: 99%